P5-S6.36 Factors affecting quality of life of people living with HIV In Karnataka, India. (10th July 2011) - Banandur, P; Becker, M L; Garady, L; Yallappa, A; Isaac, S; Potty, R S; Washington, R G; Blanchard, J F; Moses, S; Banadakoppa, R M
Abstract : Background: In India, stigma and discrimination in healthcare settings, poor linkages between services and lack of trained personnel affect the quality and accessibility of HIV services. In effort to both scale up and strengthen the quality and coordination of HIV care and support services in the state of Karnataka, the Samastha Project was developed. This enhanced care model uses a district based approach which integrates government services with project-based care and support services. Quality of life (QOL) is a critical outcome of HIV intervention. There is little data on the effect of HIV care and support services on QOL. We used baseline data from a 2-year prospective cohort study (QOL-Cohort study) of people living with HIV (PLHIV) in the Samastha program to identify factors affecting QOL among PLHIV. Methods: We conducted Factorial analysis using a set of key variables assumed to be associated with QOL to develop a factor score from the data collected by a face-to-face interview using a standardised questionnaire from QOL cohort study. Multivariate linear regression analysis was conducted using the factor score as dependent variable. High factor score indicated high QOL. Age, gender, locality and intensity of exposure to Samastha program were considered a priori independent variables. Factors which were associated with the outcome variable and at least one a priori independent variable were included in the final model for multivariate analysis. Results: Gender, marital status, type of housing and occupation were significantly associated with quality of life of PLHIV. Mean score (QOL) is 16.6% (ß=−0.166, 95% CI −0.31 to −0.02) lower among men compared to women. It is 31.8% (ß=−0.318, 95% CI −0.19 to −0.08) lower among widowed/divorced/separated PLHIV compared to currently married PLHIV. Mean score (QOL) is significantly lower among PLHIV who do not have a perceptible income source (ß=−0.20, 95% CI −0.36 to −0.04) compared to those with steady income. PLHIV who live in Kuccha (house built of temporary material) houses (ß=−0.26, 95% CI −0.38 to −0.14) had a significantly higher mean QOL score compared to those living in Pucca (house built of permanent material) house. Intensity of program exposure was not associated with QOL of PLHIV in this baseline survey see Abstract P5-S6.36 table 1 . Conclusions: Illiteracy, male gender, no perceptible source of income, living in a Kuccha house and being widowed, divorced or separated are associated with poor QOL among PLHIV.